1988
DOI: 10.1002/star.19880400406
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Factors Affecting Preparation of Carboxymethyl Starch

Abstract: Preparation of carboxymethyl starch using chloroacetic acid and sodium hydroxide was investigated under different conditions. The carboxymethylation reaction was studied with respect to the degree of substitution (D. S.) of the carboxymethyl starch and the reaction efficiency (R. E.) of carboxymethylation variables studied included concentration of reactants and liquor ratio as well as reaction time and temperature. D. S. and R. E. were greatly enhanced by decreasing the liquor ratio. D. S. and R. E. increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 11 publications
3
28
0
1
Order By: Relevance
“…However, a further increase in concentration of MCA beyond 2g using the optimum dose of NaOH concentration favors the glycolate formation and the reaction efficiency decreases. Similar observations are reported for Cassia tora gum, starch, Leucaena glauca seed gum and Cassia occidentalis seed gum [51][52][53].…”
Section: Optimization Of Dssupporting
confidence: 88%
“…However, a further increase in concentration of MCA beyond 2g using the optimum dose of NaOH concentration favors the glycolate formation and the reaction efficiency decreases. Similar observations are reported for Cassia tora gum, starch, Leucaena glauca seed gum and Cassia occidentalis seed gum [51][52][53].…”
Section: Optimization Of Dssupporting
confidence: 88%
“…In this context, our interest was focused on CMS with a high DS value because carboxymethylation is a versatile transformation leading to water-soluble polymers and intermediates with various valuable features. [2][3][4] The properties (e.g., solution viscosity, film formation, cation interaction, and supramolecular aggregate formation) are mainly determined by the total DS, that is, the average number of carboxymethyl functions in the polymer. Moreover, the functionalization pattern may influence the properties.…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum presents several disadvantages for wet milling such as the presence of peripheral endosperm which acts as a barrier against the penetration of the steep solution, a harder protein matrix and crosslinking which engulfs starch granules thus lowering yields and starch quality. The leaching of phenolic pigments present in the pericarp, testa, and aleurone tissues produce off-colored starch [1][2][3][4][5]. Several researchers have found that sorghum generally yields about 10 % less prime starch than corn [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Carboxymethylation of polyglucans such as starch and cellulose is a versatile transformation since it provides access to water-soluble polymers and intermediates with various valuable features [1][2][3][4][5]. The properties of carboxymethylated polyglucans (viscosity, interaction with multivalent cations or polycations, and the formation of supramolecular aggregates) are mainly determined by the degree of substitution (DS), i. e. the average number of carboxymethyl functions per repeating unit.…”
mentioning
confidence: 99%